2019
DOI: 10.1097/coc.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Curative-dose Chemoradiotherapy Versus Total Laryngectomy For Stage T3-T4 Squamous Cell Carcinoma of the Larynx

Abstract: Objective: Chemoradiotherapy (cRT) and total laryngectomy (TL) are acceptable treatments for locally advanced laryngeal squamous cell carcinoma (LSSC). We aimed to compare the outcomes in patients receiving full-dose treatment. Methods: We identified 11,237 patients in the National Cancer Database treated 2004 to 2015 for T3-4N0-3 LSCC with either TL (with 60 to 80 Gy of adjuvant RT) or cRT (70 to 80 Gy). We evaluated differences in overall survival (OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 21 publications
1
41
0
3
Order By: Relevance
“…It is clear that patients with higher nodal category perform poorly regardless of treatment modality, and this poses a challenging problem particularly for advanced LC. In this scenario, while CRT is associated with worse OS compared to TL in some patients with T4 disease, no difference is seen among patients with T3 LC with minimal cartilage erosion, regardless of N status [ 21 ]. Dissecting these specific patients accurately, Choi at al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that patients with higher nodal category perform poorly regardless of treatment modality, and this poses a challenging problem particularly for advanced LC. In this scenario, while CRT is associated with worse OS compared to TL in some patients with T4 disease, no difference is seen among patients with T3 LC with minimal cartilage erosion, regardless of N status [ 21 ]. Dissecting these specific patients accurately, Choi at al.…”
Section: Discussionmentioning
confidence: 99%
“…However, in pN1 LSCC, based on our results and some emerging evidence, even if it is not strictly indicated by the NCCN Guideline, the use of PORT might be considered. To the best of our knowledge, despite no survival differences were seen in T3 N0 or T3 N+ comparing TL+ PORT and CRT, the role of PORT is controversial in the subgroup of surgically treated T3N1, even retrieving the data from the largest and most comprehensive population-based studies [ 21 , 42 ]. We hope that further study will clarify if this very specific subset of patients might benefit or not of adjuvant treatment, or even curative RT/CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Although showing superior overall survival after primary chemoradiotherapy vs. primary surgery in the univariate analyses, the statistical significance of treatment modality was lost in the multivariate analyses. Similarly, no survival benefit with one treatment modality to another in N0 or N+ subgroups could be demonstrated, but Timmermans et al [99] showed an impaired five-year overall survival in T3N+ compared to T3N0 tumors. Smaller retrospective chart reviews on patients treated within the last two decades corroborate these findings [99][100][101].…”
Section: Oncologic Outcomementioning
confidence: 99%
“…The study by Timmermans et al [99] compared survival according to staging (T3 vs. T4) and to treatment modality (total laryngectomy with adjuvant radiotherapy vs. chemoradiotherapy) and showed no difference for either of the two. However, the majority of T3 tumors were treated with organ-preserving chemoradiotherapy and the majority of T4 tumors were treated with total laryngectomy and adjuvant irradiation.…”
Section: Oncologic Outcomementioning
confidence: 99%
“…Como utilizaram diferentes populações, eles entraram de maneira diferente na análise. No caso, o estudo de Patel et al98 foi utilizado na análise de sobrevivência geral, enquanto o de Nocon et al96 foi utilizado para sobrevivência geral excluindo casos T2, e o de Bates et al97 foi utilizado nos índices de sobrevivência T3 e T4 separados. O estudo de Stokes et al87 não foi utilizado por utilizar população semelhante aos outros estudos.…”
unclassified